Formação continuada de diretores de escola: afinal, o que os diretores precisam saber? - Caputi, Débora Rosangela Philomeno (2022)
The objective of this dissertation was to investigate the relationship established by the school principal with continuing education, the perceptions of this professional about the offered and the school reality and about the contribution of continuing education in the construction of their role. The theoretical foundation is based on Lück (2000, 2009 and 2015); Libâneo (2018); Paro (2012 and 2016); Marin (2019); Alonso (1976); Imbernón (2011) and Tardif (2014). The research subjects are school principals of the Guarulhos City Hall. The methodology applied in the research is Qualitative Research. Data were collected through semi-structured interviews. The hypothesis was that the various dimensions of school management, especially the pedagogical dimension, are poorly addressed in the continuing education of school principals. The analysis confirmed the hypothesis. The three research questions were: do school principals perceive any relationship between the educational proposal and the school reality? Do the continuing education activities contribute to the formation of the school principal's identity? After all, what do principals need to know? After the investigation, the results showed that: a) the school directors do not perceive the relationship between the formation and the school reality, but wish that this relationship happens; b) the formative actions did not bring contributions to the subjects in the formation of the school director identity; c) what the directors need to know involves all the school management dimensions. The study is scientifically relevant for bringing reflections on the educational field and the spheres of planning and implementation of public policies, especially those that affect the organization of schools, as a field of action for school principals. As an important link in public policy and a comprehensive professional field, school management influences the quality of learning and teaching and has a structural function in the organization of school dynamics. As a central and not centralizing subject, the school principal articulates and intermediates to achieve the quality of internal and external educational processes to the school, and the continuous critical and dialogical reflection is necessary to his or her pedagogical work